The Use of Quizwhizzer-Based Learning Media to Increase Class XI Students’ Learning Interest in Economics Subjects at SMAN 1 Mandau - Fitriani, Ulfa; Suarman, Suarman; Mujiono, Mujiono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
The present study analyzes the differences in students' learning interests before and after using quizwhizzer-based learning media. This research was carried out at SMAN 1 Mandau in class XI in the economics group. The research uses an experimental method with the One Group Pretest-Posttest Design model. The data collection method uses a questionnaire, and the data analysis technique uses descriptive statistical analysis and difference tests (t-test). The research results show that there are differences in students' learning interests before and after using quizwhizzer-based learning media. This is proven by the pretest results of interest in learning of 67.63, where students were quite interested in participating in learning before using quizwhizzer-based learning media. Then, after using quizwhizzer-based learning media there was a change in students' interest in learning, which increased to 73.62, which means that learning media quizwhizzer-based can increase students' interest in learning. The results of the different tests (t-test) show that the tcount value obtained is 6,912 while the ttable value is 1,692, so the tcount > ttable value so it can be concluded that there is a difference in students' learning interest before and after using quizwhizzer-based learning media. Thus, teachers are expected to be able to use this media during the learning process because quizwhizzer-based learning media can increase students' interest in learning. This research can be a reference for increasing students' interest in learning. And future researchers can use premium quizwhizzer-based learning media to obtain features more complete.